Role of extension service in implementation of agricultural and environmental programmes in Podkarpacie region - Miś, Teresa (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
Importance of extension ervices in the realization of agricultural and environmental undertakings in Podkarpacie region is assessed. Results obtained from the study indicate that farmers in Podkarpacie are actively searching funds for and participating in agricultural and environmental programmes. Agricultural and environment advisors play important role in that process, mainly by organizing training workshops, as well as by preparing respective applications and agricultural and environmental plans.